2019
DOI: 10.1107/s2053229619004236
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric diosmium sawhorse complexes

Abstract: Three asymmetric diosmium(I) carbonyl sawhorse complexes have been prepared by microwave heating. One of these complexes is of the type Os2(μ-O2CR)(μ-O2CR′)(CO)4 L 2, with two different bridging carboxylate ligands, while the other two complexes are of the type Os2(μ-O2CR)2(CO)5 L, with one axial CO ligand and one axial phosphane ligand. The mixed carboxylate complex Os2(μ-acetate)(μ-propionate)(CO)4[P(p-tolyl)3]2, (1), was prepared by heating Os3(CO)12 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The symmetric diosmium carbonyl sawhorse complex, Os 2 (u-O 2 CR) 2 (CO) 6 , features a diosmium center with two cis -carboxylate bridging ligands and six carbonyl ligands occupying the remaining equatorial and terminal positions. Recent studies have shown an unexpected mechanism for the 12 CO/ 13 CO exchange of the terminal carbonyls, which is kinetically zero order in [ 13 CO] but involves a very weakly bound interchange transition state . One or both weakly bound terminal COs can be easily replaced by other ligands such as phosphines, pyridines, and nitriles. , A wide-ranging study of multiple new asymmetric diosmium sawhorse complexes, Os 2 (u-O 2 CR) 2 (CO) 6– n (P­( p -tolyl) 3 ) n ( n = 0, 1, or 2 and R = H, CH 3 , CH 2 CH 3 , or C 6 H 5 ), revealed linear relationships between their C eq –Os–Os–C eq dihedral angles and Os–Os bond distances . These linear relationships appear as two separate parallel trendlines, either with or without terminal phosphine(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symmetric diosmium carbonyl sawhorse complex, Os 2 (u-O 2 CR) 2 (CO) 6 , features a diosmium center with two cis -carboxylate bridging ligands and six carbonyl ligands occupying the remaining equatorial and terminal positions. Recent studies have shown an unexpected mechanism for the 12 CO/ 13 CO exchange of the terminal carbonyls, which is kinetically zero order in [ 13 CO] but involves a very weakly bound interchange transition state . One or both weakly bound terminal COs can be easily replaced by other ligands such as phosphines, pyridines, and nitriles. , A wide-ranging study of multiple new asymmetric diosmium sawhorse complexes, Os 2 (u-O 2 CR) 2 (CO) 6– n (P­( p -tolyl) 3 ) n ( n = 0, 1, or 2 and R = H, CH 3 , CH 2 CH 3 , or C 6 H 5 ), revealed linear relationships between their C eq –Os–Os–C eq dihedral angles and Os–Os bond distances . These linear relationships appear as two separate parallel trendlines, either with or without terminal phosphine(s).…”
Section: Introductionmentioning
confidence: 99%
“…The authors’ interest in this study began with the observation of variations in metal–metal bond distance and dihedral angle among newly synthesized diosmium­(I) sawhorse complexes . We were curious about the relationship between M–M bond distance, ligand type, and molecular conformation, initially wondering whether the basicity of the bridging ligands was the defining factor causing differences in M–M bonding interactions.…”
Section: Introductionmentioning
confidence: 99%